O-GlcNAcylation Is Required for the Survival of Cerebellar Purkinje Cells by Inhibiting ROS Generation - Fengjiao Liu; Shen Li; Xin Zhao; Saisai Xue; Hao Li; Guochao Yang; Ying Li; Yan Wu; Lingling Zhu; Liping Chen; Haitao Wu (MDPI AG, 2023)
Purkinje cells (PCs), as a unique type of neurons output from the cerebellar cortex, are essential for the development and physiological function of the cerebellum. However, the intricate mechanisms underlying the maintenance of Purkinje cells are unclear. The O-GlcNAcylation (O-GlcNAc) of proteins is an emerging regulator of brain function that maintains normal development and neuronal circuity. In this study, we demonstrate that the O-GlcNAc transferase (OGT) in PCs maintains the survival of PCs. Furthermore, a loss of OGT in PCs induces severe ataxia, extensor rigidity and posture abnormalities in mice. Mechanistically, OGT regulates the survival of PCs by inhibiting the generation of intracellular reactive oxygen species (ROS). These data reveal a critical role of O-GlcNAc signaling in the survival and maintenance of cerebellar PCs.